Optimalisasi Seni dan Budaya dalam Mitigasi Teror dan Radikalisme - Febriyando (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article focuses on optimizing art and culture in mitigating terror and radicalism. This study uses a qualitative method. Referring to literature studies, primary and secondary, designed, mapped based on reference data processing, presented as a limiting comparison material and then abstracted, which aims to understand the quality of art and culture learning in mitigating terror and radicalism. The results of the study show that learning art and culture is not only learning that focuses on didactic knowledge, but also plays a role in humanist behavior. Learning Arts and culture is able to encourage productivity in differences without objects. The potential for learning arts and culture to be developed in mitigating terror and radicalism.